THE IMPORTANCE AND PURPOSE OF STUDYING LATIN IN MEDICAL SCHOOLS - Shirinkulova Shafoat Malikovna (Bright Mind Publishing, 2026)
The article analyzes the role of Latin in medicine in the modern era. Latin is the main language of the Catholic religion and is used in medicine to form anatomical, clinical and pharmaceutical terms. The role of Latin in the formation of Western European languages and in enriching the Russian language with borrowed words, winged and professional expressions is very large.
Keywords: International terminology, international terminology, professional language, professional, anatomical, clinical, pharmaceutical, aphorism, knowledge, skills.